The economic microgeography of diversity and specialization - Martin Andersson; Johan P. Larsson; Joakim Wernberg (Research Institute of Industrial Economics (IFN), 2017)
As cities increasingly become centers of economic growth and innovation, there is a need to understand their inner workings and organization in greater detail. We use ge-coded firm-level panel data at the sub-city level to assess the long-standing question whether agglomeration economies derive from specialization (within-industry) or diversity (between-industry). We show that these two types of externalities co-exist, but differ in their spatial distribution and attenuation within cities. There are robust positive effects of diversity and specialization on firms' TFP growth at the local within-city neighborhood level, especially for firms in high-tech and knowledge-intensive activities. While specialization effects are bound to the local sub-city level, we demonstrate a positive effect of overall diversity also at the city-wide level. The results resonate with the idea that urban economies provide a mix of industrial diversity and specialisation. A location in a within-city industry cluster in a diversified, large city appears to let firms enjoy the benefits of local industry-specific externalities, while reaping the general city-wide benefits of a diversified city.
Keywords: R12; D24; L23; 330; productivity; diversity; specialization; externalities; knowledge spillovers; attenuation; agglomeration economies; geocoding